COVID-19 in Asia law and policy contexts - Ramraj, Victor Vridar 1968- (Oxford University Press, 2020)
This is a book for an extraordinary time, about a pandemic for which there is no modern precedent. It is an edited collection of original essays on Asia's legal and policy responses to the COVID-19 pandemic, which, in a matter of months swept around the globe, infecting millions. It transformed daily life in almost every corner of the planet-from the empty streets of once-bustling Mumbai to the silent 2020 Olympic Games venues of Tokyo. In a matter of weeks, the unimaginable became ordinary: lockdowns of cities and entire countries, physical distancing and quarantines, travel restrictions and border controls, movement-tracking technology, mandatory closures of all but essential services, economic devastation and mass unemployment, and government assistance programs on record-breaking scales. Yet a pandemic on this scale, under contemporary conditions of globalization, has left governments and their advisors scrambling to improvise solutions, often themselves unprecedented in modern times, such as the initial lockdown of Wuhan. This collection of essays analyzes law and policy responses across Asia, identifying cross-cutting themes and challenges. It taps the collective knowledge of an interdisciplinary team of sixty-one researchers both in the service of policy development, and with the goal of establishing a scholarly baseline for research after the storm has passed. The collection begins with an epidemiological overview and survey of the law and policy themes. This jurisdiction-specific case studies and cross-cutting thematic essays cover five topics: first wave containment measures; emergency powers; technology, science, and expertise; politics, religion, and governance; and economy, climate, and sustainability"--